The Effect of Product Quality, Customer Service, Operational Processes, and Work Environment on Customer Loyalty in Insurance Companies (Pusat Riset dan Inovasi Nasional, 2026)
This study was inspired by the vital importance of customer loyalty in maintaining the long-term sustainability of insurance companies, particularly amid the increasingly competitive dynamics of the industry. It identifies four major factors that are believed to have both direct and indirect impacts on customer retention and corporate reputation: product quality, customer service, operational efficiency, and the work environment. The research adopts a quantitative approach, utilizing surveys distributed to active customers of PT Jasaraharja Putera, Jayapura Branch. The collected responses were statistically analyzed to assess both the individual and combined effects of each variable on customer loyalty. The results indicate that these four dimensions are interconnected and collectively shape the level of customer loyalty. High-quality and transparent products foster initial trust, while fast and responsive service turns expectations into positive experiences. Streamlined operational procedures ensure consistent fulfillment of service commitments, and a supportive workplace environment enhances employee motivation and performance, leading to superior service delivery. Empirical evidence from the study suggests that strengthening customer loyalty requires a comprehensive and integrated approach. Insurance firms should design products that align with customer needs, deliver empathetic and efficient service, optimize operational processes for greater effectiveness, and cultivate a positive work culture that motivates employees. Beyond its managerial implications, this research enriches the academic discourse on customer loyalty by highlighting the role of internal organizational factors within financial service institutions. Practically, the study provides strategic insights for management in formulating more focused and data-driven policies. The findings are expected to help insurance companies not only retain their current clients but also attract new ones by enhancing their reputation, service quality, and overall customer experience.